Maximising Olympic Distance triathlon performance: A sports dietitian's perspective - Hellemans, I. (Proceedings from the Gatorade International Triathlon Science II Conference, Noosa, Australia, November 7-8, 1999: Maximising Olympic Distance Triathlon Performance: A multi-disciplinary perspective, 1999)
Nutrition is a key factor in maximising Olympic Distance Triathlon performance. The role of nutrition is to maintain health, support training, maximise performance, enhance recovery and achieve optimum body composition and weight. Triathletes and their coaches are advised to develop nutrition plans for training and competitition based on current scientific information, adapted to individual needs and specific training and competition situations. It is important that supplement plans are an integral part of an overall dietary strategy, rather than being considered in isolation. Fad diets need to be avoided as they have no proven benefit and may have adverse effects.